THE USE OF GENERIC MOXONIDINE IN SYSTEMIC BLOOD PRESSURE ELEVATION - B. B. Ruksin; O. B. Grishin; S. V. Yashchenkova; М. В. Onuchin (Кардиоваскулярная терапия и профилактика, 2015)
Aim. To evaluate the opportunities of the Tenzotran generic moxonidine for urgent care in non-life-threatening blood pressure (BP) increase; to check the efficacy, safety and duration of sufficient effect onset. Material and methods. The study is performed in pre-hospital stage with participation of 53 patients with BP increase, non-life- threatening. The 1st group consisted of the patients with clinical signs of hyper sympathetic activity, the 2nd — patients with the signs mentioned.Moxonidine generic was prescribed sublingually once in dosage 0,4 mg. Then the signs were collected for increased sympathic activity, BP, heart rate, localization and severity of headache, adverse events.Results. In emergency care Tenzotran effectively decreases blood pressure ad relieves headache in patients with the signs of increased sympathetic tone. Adverse events after Tenzotran use are not severe and are rare. Conclusion. Confirmed effectiveness and safety make it possible to recommend moxonidine generic Tenzotran for emergent care in BP increase that is non-life-threatening, in outpatient care.